Subtitusi Terigu dengan Pati Garut (Maranta Arundinaceae L) pada Pembuatan Roti Tawar - Husniarti HUsniarti; Indiyah S. Utami; Siti Rahayu (agriTECH, 2001)
The objective of this research was to find out the effect of substitution of wheat flour with arrwroot starch on textural characteristic of bread. Arrowroot starch used to substitute wheat flour was at 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100% respectively. The physical characteristics of mixed flour was analyzed using Farinograph. The result showed that the increasing proportion of arrowroot starch in the composite decreased in the peak consistency and dough stability. Substitution wheat floyr with arrowroot starch at 0% - 40% could be used in bread making. Based on extensogram, substitution of wheat flour with arrowroot starch at 0%, 10%, 20%, 30% and 40% showed that the increasing proportion of arrowroot starch decreased in resistancy, extensibility and the rasio of resistency and extensibility of the dough. The fermentation time for bread making was 45-90 minutes. The textural characteristic of bread was measured using Lloyd Universal Testing Machine and the density by displacement test method. The result showed that increasing of arrowroot starch proportion increased in density and hardness of bread but decreased the cohesivity.